Sadashiva Temple (Temple 4) of Cluster 2 of the Temple Complex - Temples of India Project Team (Jio Institute, 2024)
The Sadashiva Temple has a pitha (a small platform) and a vedibandha (basal mouldings), consisting of khura, kumbha (pot-shaped), kalasha (a pitcher), antarapattika (recesses between moulding), and kapotapalika (cyma recta moulding). The jangha (wall) is plain but adorned with a central horizontal band of kirtimukha (face of glory). The superstructure of the temple is of the latina style (mono-spired).